2019
DOI: 10.1126/science.aav8197
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a bHLH transcription factor allowed almond domestication

Abstract: Wild almond species accumulate the bitter and toxic cyanogenic diglucoside amygdalin. Almond domestication was enabled by the selection of genotypes harboring sweet kernels. We report the completion of the almond reference genome. Map-based cloning using an F1 population segregating for kernel taste led to the identification of a 46-kilobase gene cluster encoding five basic helix-loop-helix transcription factors, bHLH1 to bHLH5. Functional characterization demonstrated that bHLH2 controls transcription of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 78 publications
5
108
0
1
Order By: Relevance
“…The group of SNPs identified in the present study could prove useful for various marker-based applications in Prunus. In fact, the genus Prunus is well enabled with the availability of several reference genome sequences 25,26,[46][47][48][49] . However, it must be noted that each genome is prone to harbor insertions and deletions with respect to genomes from other species.…”
Section: Discussionmentioning
confidence: 99%
“…The group of SNPs identified in the present study could prove useful for various marker-based applications in Prunus. In fact, the genus Prunus is well enabled with the availability of several reference genome sequences 25,26,[46][47][48][49] . However, it must be noted that each genome is prone to harbor insertions and deletions with respect to genomes from other species.…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of long-read sequencing technologies and long-range scaffolding methods has enabled chromosome-scale assembly for multiple plant species, including highly heterozygous tree crops such as almond ( Prunus dulcis ; (Sánchez-Pérez et al 2019) and kiwifruit ( Actinidia eriantha ; (Tang et al 2019). The availability of genomes with fully assembled chromosomes provides foundations for understanding plant domestication and evolution (Jarvis et al 2017; Maccaferri et al 2019; Sánchez-Pérez et al 2019), the mechanisms governing important traits (e.g. flower color and scent; (Raymond et al 2018), as well as the impact of epigenetic modifications on phenotypic variability (Daccord et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more researches reveal that bHLH gene play important role in fruit development process, including tomato [11], peach [19], apple [20], almond [33] and Chinese jujube [34]. In this study, 91 HrbHLH mRNAs had an RPKM value greater than 1 in three fruit development stages.…”
Section: Discussionmentioning
confidence: 63%
“…The expression HrbHLH90 was signi cantly higher at the early stage of fruit development. This result also indicated that it might be involved in fruit enlargement [26,33]. In addition, the expression of HrbHLH91 and HrbHLH92 were signi cantly higher at the ripen stage of fruit development.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation